ססע־תיהם של מלכי מיסיפיטאמיה לחוף דשיניקי לפני הקתת האימפריה האשלרים - Malamat, Avraham (1965)
אברהם מימט; The Campaigns of the Mesopotamian Kings to the Phoenician Coast before the Rise of the Assyrian Kmpire; Western Galilee and the Coast of Galilee.